Systematics and historical biogeography of Neotropical foam-nesting frogs of the Adenomera heyeri clade (Leptodactylidae), with the description of six new Amazonian species - Carvalho, Thiago R.D. [UNESP]; Moraes, Leandro J.C.L.; Lima, Albertina P.; Fouquet, Antoine; Peloso, Pedro L.V.; Pavan, Dante; Drummond, Leandro O.; Rodrigues, Miguel T.; Giaretta, Ariovaldo A.; Gordo, Marcelo; Neckel-Oliveira, Selvino; Haddad, Célio F.B. [UNESP] (Oxford University Press (OUP), 2021)
A large proportion of the biodiversity of Amazonia, one of the most diverse rainforest areas in the world, is yet to be formally described. One such case is the Neotropical frog genus Adenomera. We here evaluate the species richness and historical biogeography of the Adenomera heyeri clade by integrating molecular phylogenetic and species delimitation analyses with morphological and acoustic data. Our results uncovered ten new candidate species with interfluve-associated distributions across Amazonia. In this study, six of these are formally named and described. The new species partly correspond to previously identified candidate lineages 'sp. F' and 'sp. G' and also to previously unreported lineages. Because of their rarity and unequal sampling effort of the A. heyeri clade across Amazonia, conservation assessments for the six newly described species are still premature. Regarding the biogeography of the A. heyeri clade, our data support a northern Amazonian origin with two independent dispersals into the South American Dry Diagonal. Although riverine barriers have a relevant role as environmental filters by isolating lineages in interfluves, dispersal rather than vicariance must have played a central role in the diversification of this frog clade.
Keywords: bioacoustics; biodiversity; Brazil; distribution patterns; diversification; Dry Diagonal; riverine barriers; South America